Silvipastoral approach to improve productivity of native pastures for improved livestock production in mid hills of Western Himalaya - DEV, INDER; KHOLA, O P S; RADOTRA, SUDESH; SAREEN, SINDHU; MISRI, BIMAL; SRIVASTAVA, A K; SHARMA, S K (The Indian Journal of Animal Sciences, 2012)
Animal husbandry, an integrated component of hill agriculture has caused severe land degradation due to continuous grazing and massive reduction in the vegetation cover. The feeding of livestock depends primarily on natural resources, viz. grasslands, forests, cultivated fodder, field bunds, crop residues, weeds and fodder trees. The silvipasture laid out at 3 sites, viz. Ghanetta (1100 m above msl), Dagoh (1020 m above msl) in Kangra district and Jogindernagar (1175 m above msl) in Mandi district of Himachal Pradesh had a slope of 15–35%, 25–60% and 15–30%, respectively. Silipastures were laid out with active participation of native beneficiaries. Survival rate of Bauhinia variegata, Morus alba and Grewia optiva was highest (90% and above) at all the 3 sites. Growth in terms of height gained by the fodder trees was similar at all the 3 sites. At the end of third year, the 2- year-old saplings transplanted at all the 3 sites, Albizia attained a height of about 200 cm, Artocarpus (110 cm), Bauhinia (150 cm), Grewia (120 cm) and Morus (130 cm). During third year of the study fresh biomass of 31.6, 28.6 and 30.8 t/ha were harvested from Ghanetta, Jogindernagar and Dagoh with dry matter yield of 8.67, 6.98 and 7.62 t/ha, respectively. Crude protein was in the range of 12.33 to 13.46% due to grass legume mixture. The average body weight gain ranged from 358.50 to 388.53 g/day in indigenous male cattle. Runoff (% of rainfall) was higher at Jogindernagar (33.4%) followed by Dagoh (29.9%) and Ghanetta (20.4%) owing to their land slopes. Cut and carry system was most efficient at all the sites allowing only 15.8% runoff compared to 20.6% and 27.1%, respectively under controlled and traditional grazing. Among the resource conservation measures, trenching in combination with vegetative barrier allowed only 6.8% of rain as runoff compared to 38.9% under control (no measure). Trenches formed in upper, middle and lower parts along the slope retained on an average 13.9, 16.6 and 19.1 cm sediments, respectively. Among the sites, the sediment retention was highest at Dagoh (18.7 cm) followed by Joginder Nagar (16.9%) and lowest at Ghanetta (14.0 cm). Therefore, silvipasture seems to be one of the best options for regenerating and improving the Himalayan grasslands. The system can enhance the forage availability many fold, which can assure the sustainability of on-going livestock rearing and in the process the resource base gets conducive inputs for its conservation.